Urgensi Manajemen Konflik Di Perpustakaan: Sebuah Sistematik Review - Rodin, Rhoni; Afrina, Cut (IQRA`: Jurnal Perpustakaan dan Informasi, 2023)
The purpose of this writing is to analyze the extent of the urgency of conflict management in the library. Research method with literature study. The results of the research show that conflict management is very important in the library. Every organization must experience conflict, and the library is no exception. Therefore, conflict management is very urgent in the library. This urgency is shown in terms of the benefits that will be obtained by the library if the conflict can be managed properly. So that a conflict does not occur protractedly, it is necessary to prevent or resolve the conflict so that it does not have a negative impact on the running of the library organization, including: 1) The need for massive and structured socialization of the librarian's Code of Ethics; 2) The need for awareness about the main duties of librarians; 3) The importance of librarians mastering interpersonal communication skills. The ability of librarians in conducting interpersonal communication is currently a necessity that cannot be denied and postponed again considering the duties of librarians who provide services to the general public so that this becomes a special need and skill for librarians. Conflict management properly will limit the negative aspects and even be able to increase the positive aspects of conflict in a library